Sodobne raziskave o poučevanju glasbe v Sloveniji (University of Maribor Press, 2024)
Contemporary Research on Music Education in Slovenia. The monograph "Contemporary Research on Music Education in Slovenia" covers a wide range of topics related to music education at various educational levels in 15 chapters. It sheds light on the importance of music didactic games in the development of preschool children’s musical abilities, the impact of musical activities on social interactions in early childhood, and the challenges of integrating music and dance activities in Montessori kindergartens. It investigates the cross-curricular integration of music and visual arts, the challenges of planning music lessons, musical creativity in primary schools, and the incorporation of music therapy elements. It examines the representation of musical genres in young people’s novels, the role of teachers in fostering talent development, the use of interactive learning materials, technology in music education, the optimal motivating environment in music schools, the formation of a musical self-image, and the peculiarities of music education in the Slovenian region of Istria. The results of the current research contribute to the advancement of the field of music didactics and serve as the foundation for the improvement of "music" practice in the Slovenian education system.